Milk Production An Up-to-Date Overview of Animal Nutrition, Management and Health - Chaiyabutr, Narongsak (IntechOpen, 2012)
Book "Milk Production - An Up-to-Date Overview of Animal Nutrition, Management and Health" is organized into three main sections, and is concerned with the animal nutrition, animal management and, breeding and animal health. This book permits the reader's exposure to the expert's experience and scientific style of interpreting and integrating available data into his own views. This book will be useful for students, researchers, teaching staff, practicing professionals connected with dairy science, animal science, food science, nutrition, physiology, biochemistry, veterinary medicine and other related fields. Each chapter in this book has an extensive bibliography which can future aid the reader in keeping abreast of the developments in this field.